The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1074/jbc.m112.385369
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and Extracellular ATP Coordinately Regulate the Inverse Correlation between Osteoclast Survival and Bone Resorption

Abstract: Background: Mature osteoclasts with a spontaneous tendency toward apoptosis resorb bone efficiently during their short lifespan. Results: Released ATP from intracellular stores has a negative impact on the bone resorption activity of osteoclasts by altering their cytoskeletal structures. Conclusion: ATP depletion leads to osteoclastic bone resorption. Significance: This study provides a new direction for investigating the mechanisms involved in physiological and pathological bone resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 66 publications
4
92
1
1
Order By: Relevance
“…Extracellular ATP levels control and modulate the activity of both the osteoblasts (Orriss et al, 2013) and the osteoclasts (Miyazaki et al, 2012), implying that the nucleotides released by osteoblasts in bone could locally affect mineralization. By contrast, in vitro through special transporters, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular ATP levels control and modulate the activity of both the osteoblasts (Orriss et al, 2013) and the osteoclasts (Miyazaki et al, 2012), implying that the nucleotides released by osteoblasts in bone could locally affect mineralization. By contrast, in vitro through special transporters, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…4,35 The released ATP negatively regulated bone-resorbing activity through an autocrine/paracrine feedback loop. 21,30 When the extracellular ATP was hydrolyzed by nucleotidase apyrase, the micropipette indentationinduced elevation of [Ca 2+ l i didn't change, indicating that nucleotide release is not essential for mechanically induced Ca 2+ influx. 42 We blocked the binding of ATP to the purinergic receptor with suramin and found that responsive percentage of osteoclasts decreased at low FSS level while almost all of cells responded for high FSS level (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies suggest that components of ATP synthase are also present on the outer surface of the plasma membrane, where they function as receptors for various ligands and are known to be involved in lipid formation, the regulation of endothelial cell proliferation and differentiation, and immune responses in tumor cells (82)(83)(84)(85). It is also known that intracellular ATP levels regulate the inverse correlation between osteoclast survival and bone resorption through an unknown mechanism, and that extracellular ATP likely exerts inhibitory effects on osteoclast survival and the bone remodeling and resorption induced by mature osteoclasts through the alteration of cytoskeletal structures (86).…”
Section: Discussionmentioning
confidence: 99%